Outsource agrifood service MSMEs facilitating pivoting by fruits & vegetables farmers, wholesalers, and retailers - Reardon, Thomas; Awokuse, Titus; Liverpool-Tasie, Lenis Saweda O.; Minten, Bart; Nguyen, Geneviève; Qanti, Sara; Swinnen, Johan; Vos, Rob; Zilberman, David (International Food Policy Research Institute, 2024)
There is an important gap in the literature regarding evidence about the emergence of outsource agrifood services. We contend that there are few studies on outsource services for differentiated product value chains, particularly in developing countries. To some extent, also, there is a knowledge gap regarding the use and effectiveness of eco-certification and labeling compliance-assisting services in developed countries. The bulk of attention on outsource services is centered at the commodity phase (such as with bulk grains) and the modern stage, and less attention is being paid to the product differentiation phase. To fill these voids, we focus on three country illustrations, ranging in the product cycle phases from transitional to transitional-modern to modern, and from early differentiating case in Ethiopia (on basic quality) to intermediate differentiating case in Indonesia (on advanced quality and variety differentiation in mangoes), to advanced-differentiating case in France (on eco-labeling and certification). We focus on horticulture as it is rapidly growing, and rapidly differentiating both in developed and developing countries. We conclude that policies and public investments facilitating the formation of these services are important. Importantly, we found that without these emerging outsource services, farmers would not have been able to be resilient to the shocks of market requirements and climate change.